Performa Molting dan Sintasan Lobster Air Tawar Cherax quadricarinatus yang Diberi Dosis Dicalsium Phosphate yang Berbeda - Dwi Rachmat Budi Santoso; Firmansyah Bin Abd Jabbar; Andi Arham Atjo; Nur Indah Sari Arbit (Jurnal Perikanan Unram, 2024)
The composition of feed plays a critical role in determining growth and survival rate in aquaculture species. Freshwater crayfish, specifically Cherax quadricarinatus, is a high-value aquaculture commodity; however, cultivation is often limited by slow growth rates and high mortality. This study aimed to evaluate the effects of incorporating dicalcium phosphate (DCP) into the feed on molting frequency, growth, and survival of C. quadricarinatus. The experiment, conducted over 30 days at the Seppong Matakali Freshwater Fish Seed Center in Polewali Mandar, West Sulawesi, employed a completely randomized design with four DCP treatments (0% (A), 2% (B), 4% (C), and 6% (D) each with three replications. Data were collected on key metrics including absolute weight growth, absolute length growth, molting frequency, survival rate, specific growth rate, and feed conversion ratio. The findings indicated that the optimal performance was achieved with 4% DCP, resulting in a molting frequency of 0.77, absolute weight gain of 6.18 g, and absolute length gain of 0.92 cm. However, the highest survival rate of 90% was observed with the 6% DCP treatment.